Mothers' Partnerships, Men in the Home, and Adolescents' Secondary Exposure to Violence. Issue 4 (12th May 2018) - Crosnoe, Robert; Stritzel, Haley; Smith, Chelsea; Cavanagh, Shannon E.
Abstract : Family instability means that many U.S. youth spend time without biological fathers and with other men. This study extends the literature on the developmental implications of living with fathers and father figures by investigating the association between the presence of mothers' male romantic partners in the home and secondary exposure to violence with a focus on variability according to the identities of the men and the communities of the family. Fixed effects models of multilevel data from the Project on Human Development in Chicago Neighborhoods ( N  = 2, 201) revealed that living with mothers' partners did not have a general protective or risky association with youths' secondary exposure to violence. This exposure, however, was lower when such men were youths' biological fathers (vs. social fathers) and when they were married to (vs. cohabiting with) youths' mothers. The link between men's marital status and exposure to violence appeared stronger in higher crime neighborhoods.